2019
DOI: 10.3390/molecules24142643
|View full text |Cite
|
Sign up to set email alerts
|

Diacetylcurcumin: Its Potential Antiarthritic Effect on a Freund’s Complete Adjuvant-Induced Murine Model

Abstract: The present study aims to evaluate the antiarthritic activity of diacetylcurcumin (DAC), a synthetic derivative where the free phenolic groups of curcumin are derivatized by acetylation, thereby conferring greater lipophilicity to the parent molecule and partially overcoming the limited systemic bioavailability of curcumin. Antiarthritic activity was evaluated on a Freund’s complete adjuvant (FCA)-induced murine model of arthritis. Oral administration of DAC (60 and 120 mg/kg) resulted in a significant inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…65 Oral administration with 150 mg/kg curcumin significantly reduced paw oedema. 55 Instead, Jain et al 58 found that 62.5 mg/kg curcumin has a poor effect on the thickness of ankle joints and tail. Oral gavage and intrathecal treatment with curcumin significantly decreased mechanical allodynia and heat hyperalgesia.…”
Section: Curcumin Effect On Radiographic Scorementioning
confidence: 99%
See 2 more Smart Citations
“…65 Oral administration with 150 mg/kg curcumin significantly reduced paw oedema. 55 Instead, Jain et al 58 found that 62.5 mg/kg curcumin has a poor effect on the thickness of ankle joints and tail. Oral gavage and intrathecal treatment with curcumin significantly decreased mechanical allodynia and heat hyperalgesia.…”
Section: Curcumin Effect On Radiographic Scorementioning
confidence: 99%
“…(n = 6) 57,68,69,72,75,78 ; and Balb/c (n = 1) 58 ) or rats (Wistar (n = 1 9) 47,49,51,52,53,54,55,56,60,62,63,64,65,66,67,70,71,82,83 ; Sprague-Dawley (n = 9) 48,50,61,74,76,77,79,80,81 ; Charles Foster (n = 1) 73 and in one study there was no information about the kind of rats 59 ). The induction of RA was performed by injection of complete Freund's adjuvant (CFA) (n = 19), 47,48,49,50,51,52,54,55,63,64,65,66,67,70,73,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzyl bromide was 98% reagent grade; anhydrous potassium carbonate, dry acetone, BF 3 (Et 2 O) and ethyl ether were purchased from Sigma-Aldrich. Curcumin was obtained from natural source by usual extractive procedures and purified by crystallization [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diacetylcurcumin is a synthetic derivative of curcumin, where the free phenolic groups of curcumin have been derivatized by acetylation to confer greater lipophilicity and partially overcome the limited systemic bioavailability of curcumin [ 9 ]. The diacetylcurcumin manganese complex was a diacetylcurcumin derivative synthesized with Mn (II) as a low molecular weight compound with more potent superoxide radical scavenging activity [ 10 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%